On the Causes of Synoptic‐Scale Eddy Heat Flux Decline. Issue 24 (26th December 2022) - Park, Mingyu; Lee, Sukyoung
Abstract: The poleward heat flux by atmospheric waves plays a pivotal role in maintaining the meridional temperature gradient. A recent study found that in the Northern Hemisphere the heat flux by transient eddies has been weakening, and the study attributed this weakening to the smaller equator‐to‐pole temperature gradient caused by Arctic warming. During the period of 1979–2019 examined here, for the annual mean, both the synoptic‐scale eddy heat flux and the temperature gradient had indeed declined. However, from October to April, the synoptic‐scale eddy flux trend is more closely tied to the planetary‐scale eddy heat flux trend, than to the temperature gradient trend. From June to August, the synoptic‐scale eddy flux decline can be attributed to a warming of the high‐latitude land areas. Therefore, a more comprehensive interpretation of the synoptic‐scale eddy heat flux trend needs to include the dynamics of the planetary‐scale waves and summer land warming. Plain Language Summary: The poleward heat transport by atmospheric circulation is an important process of maintaining the meridional temperature gradient. However, a recent study showed that the heat transport by atmospheric waves in the Northern Hemisphere has been decreasing over the past few decades. As a cause of this weakening trend, the decrease of the equator‐to‐pole temperature gradient due to Arctic warming has been suggested. In this study, we examine the monthly trends of the equator‐to‐pole temperature gradient and poleward heat transport by atmospheric waves that are decomposed into synoptic‐scale waves and large‐scale waves. We find that during the winter half‐year, the trend of heat transport by synoptic‐scale waves is more closely tied to that by large‐scale waves, than to the temperature gradient trend. From June to August, it is shown that the poleward heat transport by synoptic‐scale waves decreases after a warming of the high‐latitude land areas. Therefore, these findings underscore the importance of the planetary‐scale waves and summer land warming for understanding future changes in atmospheric heat transport. Key Points: Synoptic‐scale eddy heat flux trend is strongly linked to planetary‐scale eddy heat flux trend during boreal winter and spring High‐latitude land warming leads to the decline of synoptic‐scale eddy heat flux during boreal summer Shortwave radiation plays the major role in warming high‐latitude land areas which leads to the decline in synoptic‐scale eddy heat flux